Aerial spread of smut spores during peanut harvest - Paredes, Juan Andrés (2024)
Peanut smut (Thecaphora frezzii) is one of the most important peanut diseases in Argentinian peanut production. This monocyclic soil-borne pathogen transforms kernels into spore masses. Spore liberation from broken infected pods during the harvest process is supposed to be the main mechanism of inoculum spread, with the subsequent spread among fields increasing the soil inoculum for future peanut cropping seasons. However, we are unaware of any published study on the role of wind (in terms of speed and direction) in how far smut spores spread. Therefore, we conducted an observational study where passive spore traps were distributed at harvest around six fields placed at 100, 200, 300, and 400 m away from each field’s centroid in four cardinal directions. Three time slices were sampled: from the beginning of harvest to 90-, 180-, and 270-minutes continuously during harvest. Wind speed and direction were recorded at each trap. A generalized additive model was fitted to describe the spore spread. Modeling the dispersal shows that the spread is influenced by wind speed and the smut severely damaged pods incidence present at the harvested field. Additionally, spore size and proportion of different smut spore types were assessed (from a single unit spore to a 5-multinuclear propagule). No statistical differences were observed in the proportion of the spore types trapped. However, fewer spores were trapped at distances farther from the harvested area. This work led us to understand a fundamental component of the peanut smut cycle and epidemiology, which is to design management strategies. For example, avoiding harvest on windy days (typically >10 km h-1) to prevent the distant spread of inoculum for subsequent seasons or predicting the risk surrounding an infected field.